2022
DOI: 10.1038/s41419-022-05362-y
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of METTL14 improves postmenopausal osteoporosis via IGF2BP1 dependent posttranscriptional silencing of SMAD1

Abstract: Osteoporosis (OP) tends to occur in postmenopausal women, making them prone to fractures. N6-methyladenosine (m6A) methylation plays a crucial role in OP. Herein, we aimed to explore the effects of METTL14 on osteogenesis and the underlying mechanism. Osteogenic differentiation was assessed through osteoblast markers expression, cell proliferation, ALP activity, and mineralization, which were detected by qRT-PCR, CCK-8, EdU assay, ALP staining assay, and ARS staining assay, respectively. Osteoporosis was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Postmenopausal ALP is a measure of bone formation and transformation, since release into the blood disrupts estrogen production, whereas elevated serum ALP activity reflects the activity of bone cell metabolic processes. 45 Ca and phosphorus in the blood reflect the physical structure of the bones. 46 Ca is an important mineral in the human body, of which 99% is found in the bones and teeth, and the remaining 1% is distributed in the blood, nerves, and various soft tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postmenopausal ALP is a measure of bone formation and transformation, since release into the blood disrupts estrogen production, whereas elevated serum ALP activity reflects the activity of bone cell metabolic processes. 45 Ca and phosphorus in the blood reflect the physical structure of the bones. 46 Ca is an important mineral in the human body, of which 99% is found in the bones and teeth, and the remaining 1% is distributed in the blood, nerves, and various soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…ALP is a measure of bone formation and transformation, since release into the blood disrupts estrogen production, whereas elevated serum ALP activity reflects the activity of bone cell metabolic processes 45 . Ca and phosphorus in the blood reflect the physical structure of the bones 46 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that orbital adipose tissue is a main target of the autoimmune response (36). Most RNAs exhibit m6A methylation, which regulates a range of cellular biological functions such as immunological modulation, metabolism, stem cell maintenance, and body development (37). In a previous study, we demonstrated that m6A modi cation participated in the pathogenesis of TAO using surgically excised extraocular muscles (EOMs).…”
Section: Discussionmentioning
confidence: 99%
“…Although METTL14 only engages in the complex stabilization and RNA recruitment of MTC, it could promote osteogenesis of BMSCs in physiological and pathological conditions by stimulating m 6 A modification of multiple mRNAs including PTPN6 [ 51 ], TCF1 [ 52 ], Beclin-1 [ 53 ], and SMAD1 [ 54 ].…”
Section: A Modification and Osteogenesis Of Bmscsmentioning
confidence: 99%